Features of news coverage during Covid-19 crisis: Content analysis on a sample of global news accounts on Twitter - Bin Saedan, Huda; Alhuzami, Nouf (ALBAHITH ALALAMI, 2022)
This study aims to analyze the messages of a number of global news outlets on Twitter. In order to clarify the news outlets tactics of reporting, the subjects and focus during the crisis related to the spread of the Covid-19 virus. The study sample was chosen in a deliberate manner to provide descriptive results. Three news sites were selected: two of the most followed, professional and famous international news sites: New York Times and the Guardian, and one Arab news site: Al-Arabiya channel. A total of 18,085 tweets were analyzed for the three accounts during the period from (1/3/2020) to (8/4/2020). A content analysis form was used to analyze the content of the news coverage. The results indicate an increase in the percentage of negative news related to the crisis in news coverage, and less interest in health aspects, while news related to the political aspects of the crisis received higher attention.